Effects of conditioning hops on drop jump and sprint performance: a randomized crossover pilot study in elite athletes. Issue 1 (December 2016) - Kümmel, Jakob; Bergmann, Julian; Prieske, Olaf; Kramer, Andreas; Granacher, Urs; Gruber, Markus
Abstract Background It has previously been shown that conditioning activities consisting of repetitive hops have the potential to induce better drop jump (DJ) performance in recreationally active individuals. In the present pilot study, we investigated whether repetitive conditioning hops can also increase reactive jump and sprint performance in sprint-trained elite athletes competing at an international level. Methods Jump and sprint performances of 5 athletes were randomly assessed under 2 conditions. The control condition (CON) comprised 8 DJs and 4 trials of 30-m sprints. The intervention condition (HOP) consisted of 10 maximal repetitive two-legged hops that were conducted 10 s prior to each single DJ and sprint trial. DJ performance was analyzed using a one-dimensional ground reaction force plate. Step length (SL), contact time (CT), and sprint time (ST) during the 30-m sprints were recorded using an opto-electronic measurement system. Results Following the conditioning activity, DJ height and external DJ peak power were both significantly increased by 11 % compared to the control condition. All other variables did not show any significant differences between HOP and CON. Conclusions In the present pilot study, we were able to demonstrate large improvements in DJ performance even in sprint-trained elite athletes following a conditioning activity consisting of maximal two-legged repetitive hops. This strengthens the hypothesis that plyometric conditioning exercises can induce performance enhancements in elite athletes that are even greater than those observed in recreationally active athletes.. In addition, it appears that the transfer of these effects to other stretch-shortening cycle activities is limited, as we did not observe any changes in sprint performance following the plyometric conditioning activity.